Implementing Attitudes Measurement to Influence Winter Air Pollution Mask Wearing by Pregnant Women in Ulaanbaatar: A Pilot Study - Wigfall, Clarence; Ganbat, Mandukhai; Badarch, Jargalsaikhan; Warburton, David; Crano, William D. (Central Asian Journal of Medical Sciences, 2017)
Objective: The purpose of this study is to provide an evidence based foundation to implement interventions that improve the health of the population of UB, particularly pregnant women and their yet to be born children by reducing the impact of exposure to the ultra-high air pollution levels found in the city. Methods: This is a hospital based cross-sectional survey including 35 pregnant women, 26 doctors and 31 pregnant women participated in focus groups. All participants were selected from Family Health Centers and District Hospital in UB. Results: Pregnant women both lack accurate knowledge about the effects of extreme air pollution and mask wearing and desire to have more knowledge. Health practitioners scored much higher than pregnant women, in general, on knowledge about the health implications of air pollution and the benefits of wearing air masks. Pregnant women report an overall very negative perception about wearing air masks that is more negative than their report about their perceptions of other’s negative attitudes toward those who wear air masks. Conclusion: This pilot study exposes areas that can be used in a complementary manner in the design and implementation of the more detailed full survey that will lead to the design and implementation of the planned intervention.